Kesenian Tari Soreng sebagai Media Pembelajaran Matematika: Studi Literatur Pendekatan Etnomatematika - Sofia Ika; Aziz, Abdul; Prihaswati, Martyana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
Ethnomathematics is a learning innovation that combines mathematics learning with the culture that exists in the student's environment. Learning media with an ethnomathematics approach can help students to understand mathematics through a context that is more relevant to their lives. This study aims to examine the potential of Soreng Dance as a medium for learning mathematics with an ethnomathematics approach. Data were collected through literature study techniques by studying and analyzing various literature sources, such as relevant journals and scientific articles. The results of this study indicate that the art of Soreng Dance has significant potential to be used as an interesting and effective learning media in learning mathematics. The movements and formations of dancers in Soreng Dance contain mathematical patterns and structures that can be used to teach mathematical concepts such as symmetry, comparison, and geometry. This study concludes that Soreng Dance has significant potential to be used as a medium for learning mathematics.